Proposição de um modelo processual para transformação da colaboração com universidades em empresas estabelecidas: o caso da Embraer e o ITA - Leite, Diogo Barbosa (2024)
The transformation of collaboration between established companies and universities during innovation transitions faces several challenges. To promote open innovation, companies collaborate with academic partners, facilitating the transfer of essential knowledge to develop technologies that will imply new or improved products and processes. This requires a portfolio of knowledge transfer mechanisms, such as collaborative research, contracted services, training and development programs, and shared infrastructures. Another challenge involves distributing innovation processes across different ecosystems, including knowledge ecosystems formed by universities and innovation ecosystems composed of companies. In addition, companies are fostering connections between these partners to drive innovations. This phenomenon suggests collaboration between established companies and universities can occur at multiple levels. Despite its relevance, the literature on this topic remains fragmented and poorly connected across different fronts, such as University-Industry Collaboration, Ecosystems, and Innovation Processes, with three main gaps. First, there is a lack of processual studies that analyze how the transformation of collaboration with universities evolves through the development of knowledge transfer mechanisms over time. Second, there is a lack of evidence focused exclusively on how companies foster collaboration with universities in the context of the transition to open innovation. Third, it is still unclear how focal companies can simultaneously foster interactions between universities organized in knowledge ecosystems and companies in innovation ecosystems. Given this, this study seeks to answer the question: how do established companies transform collaboration with universities during transitions to open and ecosystem based innovation? To answer this question, a qualitative exploratory study was conducted, adopting the theoretical lens of coevolution. Embraer, one of the largest aeronautical companies in the world, served as a single case study to deepen the analysis. The research included 51 interviews and 187 archival data, which allowed us to identify critical events that influenced the development of this process during the years 1996 and 2024. The data were analyzed using process data sensemaking strategies and the Gioia methodology. Based on the empirical study, the main contribution of this study is a new process model that presents four phases through which an established company fosters collaboration with universities while going through different transitions of its innovation processes: mobilization, structuring and growth, renewal, and orchestration. The phases (aggregated dimensions), processes (second-order themes), and activities (first-order categories) allow for connecting various themes and literature, revealing the dynamics of the process addressed. The results can offer managerial contributions by guiding established companies in transforming collaboration with universities and fostering strategic and lasting partnerships. The study also highlights the importance of integrating different ecosystems and facilitating connections between universities and other actors to optimize the innovation process.